2001
DOI: 10.1179/acb.2001.015
|View full text |Cite
|
Sign up to set email alerts
|

Minor Alterations in Thyroid – Function Tests Associated With Diabetes Mellitus and Obesity in Outpatients Without Known Thyroid Illness

Abstract: Thyroid function tests might be affected by diabetes and obesity. To evaluate the influence of these parameters in routine conditions, 72 diabetic and 53 non-diabetic outpatients without known thyroid diseases or severe chronic illness were recruited over a 7-month period. For each patient, dosages of thyrotropin (TSH), total and free thyroxine (TT4 and FT4, respectively), total and free triiodothyronine (TT3 and FT3) and T3 resin uptake (T3RU) were performed by radioimmunoassays. The simultaneous influence of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
19
1
1

Year Published

2002
2002
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 15 publications
3
19
1
1
Order By: Relevance
“…Ambas as condições são fatores de risco de aterosclerose e cardiopatia isquêmica e são controladas pela cirurgia bariátrica 12 . Hipotireoidismo sub-clínico ocorre mais freqüentemente em pacientes obesos e/ou diabéticos e pode ser responsável pela baixa taxa de gasto de energia em repouso encontrada em alguns pacientes obesos 13,14 . A esteatose hepática não alcoólica ocorre freqüentemente em pacientes obesos e pode progredir para cirrose hepática e insuficiência hepática.…”
Section: Discussionunclassified
See 1 more Smart Citation
“…Ambas as condições são fatores de risco de aterosclerose e cardiopatia isquêmica e são controladas pela cirurgia bariátrica 12 . Hipotireoidismo sub-clínico ocorre mais freqüentemente em pacientes obesos e/ou diabéticos e pode ser responsável pela baixa taxa de gasto de energia em repouso encontrada em alguns pacientes obesos 13,14 . A esteatose hepática não alcoólica ocorre freqüentemente em pacientes obesos e pode progredir para cirrose hepática e insuficiência hepática.…”
Section: Discussionunclassified
“…Both conditions are risk factors for arteriosclerosis and ischemic heart disease, and are controlled by gastric bypass 12 . Sub-clinical hypothyroidism is more frequent in obese and/or diabetes patients and may be responsible for the low resting energy expenditure rate found in some obese patients 13,14 Non-alcoholic fatty liver is frequent in obese patients and may evolve to liver cirrhosis and failure. Treating obesity will improve this condition.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the conflicting data available, several cross-sectional studies have shown a significant positive association between body mass index (BMI) and serum thyrotropin (TSH), even for reference range values [5,6,7]. Also there are controversial data regarding association between BMI and serum free thyroid hormones, most documenting negative association [8,9,10]. However, longitudinal surveys in this field are scarce [11,12,13,14,15,16,17].…”
Section: Introductionmentioning
confidence: 99%
“…Diabetes mellitus (DM) is the most common metabolic disorder affecting the people all over the world. It is a group of metabolic disorders characterized by hyperglycemia resulting from defect in insulin secretion, insulin action, or both [1]. It is a clinical syndrome characterized by hyperglycemia, caused by a complicated interplay of genes, obesity, environment, increased glucose production in liver, increased fat breakdown, and an absolute or relative deficiency of insulin.…”
Section: Introductionmentioning
confidence: 99%